Tren Penelitian Bulutangkis Dengan Pendekatan Psikologis: Analisis Jurnal Terindeks Garuda Menggunakan Vosviewer - Farenda, Nia; Suhariyanti, Mela; Malasari, Citra Azhariat; Bhakti, Yopi Hutomo (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This research aims to map badminton research trends with a psychological approach based on data sources from Garuda. A systematic overview of research development, including publication trends and journal publication information, by identifying research gaps to provide further research recommendations related to badminton research from a psychological approach. This research uses a descriptive quantitative method based on publication data sources obtained from Garuda and analyzed with Vosviewer. 36 nationally accredited Science and Technology Index (SINTA) journals were obtained based on research topics aligned with the writing objectives. The research results show the mapping of the distribution of publication years, mapping of publications based on journal accreditation, and mapping of research trends based on keywords (co-occurrence). It is concluded that the publication trend fluctuates from year to year, with a significant increase in 2024 (9 articles). Additionally, studies on psychology in badminton are still developing, with most research published in journals with medium accreditation. To enhance academic contributions in this field, it is recommended that future research be directed towards journals with higher accreditation and expand the scope of analysis by utilizing more data sources.